Foliar epidermal investigations in some hitherto unstudied Convolvulaceae-II - D. A. Patil, S. K. Tayade1* and (Current Botany, 2011)
The present paper contributes to the anatomy of the family Convolvulaceae.In all, six genera and 10 species have been surveyed for epidermal features in detail. They have been investigated covering stomatal type, index, frequency and number of subsidiaries, cell wall contours and cuticular striations. The leaves are amphistomatic and have commonly paracytic types, apart from rare to occasional occurrence of other stomatal types and abnormalities.